The Heroes of Olympus: The Lost Hero - Book 1 - Riordan, Rick; Stark, Janet; Sanders, Fred; Swanson, Joshua, 1978-; Listening Library ([New York] : Listening Library, 2010)
Jason, Piper, and Leo, three students from a school for "bad kids," find themselves at Camp Half-Blood, where they learn that they are demigods and begin a quest to free Hera, who has been imprisoned by Mother Earth herself.
Keywords: Mythology, Greek -- Juvenile fiction; Camps -- Juvenile fiction; Hera (Greek deity) -- Juvenile fiction; Gaia (Greek deity) -- Juvenile fiction; Monsters -- Juvenile fiction; Mythology, Greek -- Fiction; Camps -- Fiction; Hera (Greek deity) -- Fiction; Gaia (Greek deity) -- Fiction; Monsters -- Fiction; Children's audiobooks